Libel and the media : the chilling effect - Lustgarten, L.; Norrie, K.; Stephenson, H. (Oxford : Clarendon Press, 1997)
Libel and the Media is the first study to explore the impact of the law of defamation on the media. Based on extensive interviews with media lawyers, journalists, producers, and editors, it describes the efforts made by newspapers, television, book, and magazine publishers to avoid the risk of an expensive libel action - and the sorts of stories which are amended or suppressed. The authors, a distinguished group of highly respected academics, examine the present state of libel law (including the Neill reforms and the law in Scotland), and go on to give statistical information about the incidence of libel claims, and their effects on the daily work of newspapers and other media outlets.
This is an entertaining book which will appeal not only to journalists and lawyers, but also to all those with an interest in the freedom of the press and media studies generally.
1. The law of libel -- 2. The impact of libel law -- 3. National newspapers -- 4. Regional newspapers -- 5. Broadcasting -- 6. Book publishers -- 7. Magazines -- 8. The Scottish media -- 9. Conclusions.
Includes bibliographical references and index.
Keywords: Libel and slander -- United Kingdom; Mass media -- Law and legislation -- United Kingdom; Freedom of the press -- United Kingdom